EDNA metabarcoding as a means to assess distribution of subterranean fish communities: Iranian blind cave fishes as a case study. Issue 2 (9th November 2021) - Hashemzadeh Segherloo, Iraj; Tabatabaei, Seyedeh Narjes; Abdolahi‐Mousavi, Eisa; Hernandez, Cecilia; Normandeau, Eric; Laporte, Martin; Boyle, Brian; Amiri, Mohsen; GhaedRahmati, Nabiallah; Hallerman, Eric; Bernatchez, Louis
Abstract: One of the most important steps in conservation of the subterranean life forms is to decipher their distribution and ecology, which is challenging using traditional approaches. Development of an environmental DNA (eDNA) assay provides an efficient means for discovering and monitoring subterranean life forms. In this study, the distribution of three Iranian blind cave fish species (blind Iran cave barb Garra typhlops, blind Lorestan cave barb Garra lorestanensis, and blind cave loach Eidinemacheilus smithi ) was assessed using 12S rRNA eDNA metabarcoding performed using MiFish‐U PCR primers and preliminary species distribution modeling (SDM) using bioclimatic data. The majority of sampling localities with positive detection of cave barb eDNA fall within suitable habitats in the Zagros Mountains of Iran. Our results revealed that Lorestan and Iran cave barbs have differential distribution patterns, with some extent of habitat overlap in the vicinity of the originally discovered cave barb locality. According to the observed distribution patterns, the blind Lorestan cave barb and cave loach are mostly distributed in habitats close to the Sezar River (Dez River drainage, Iran), and the blind Iran cave barb is distributed towards the west and probably in a few springs in the Karkheh River drainage. Our data support the previously proposed distribution pattern for the cave barbs, in which the species show partial niche separation and reproductive isolation, with the Lorestan cave barb being a water flow‐dependent species and the Iran cave barb being a generalist species preferring variable flow rates. We showed eDNA metabarcoding to be a useful approach for ecological surveys of subterranean fish biodiversity with implications for conservation. Abstract : In this work a subterranean fish community consisting three species in the Zagros Mountains of Iran was studied using eDNA metabarcoding. The results showed differential distribution of the species in the subterranean habitats that is likely in line with previously developed hypotheses about distribution of Iran cave fish species